1999
DOI: 10.2134/agronj1999.916975x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Management in Warm Environments: Effect of Organic and Inorganic Fertilizers, Irrigation Frequency, and Mulching

Abstract: has been conducted on ameliorating the effects of heat stress through management practices.Wheat (Triticum aestivum L.) yields are reduced by heat stress in Optimal crop growth requires a nonlimiting supply many countries worldwide. The main objective of this study was to determine whether modifications to currently recommended crop of resources (water, nutrients, and radiation) and, as management practices could improve wheat yield at hot-environment temperatures rise, the demand for growth resources insites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 14 publications
2
27
0
1
Order By: Relevance
“…The results indicate that the major delay occurred at the recovery stage with delays in the subsequent stages being less and relatively constant. This is in agreement with Badaruddin et al (1999), who showed that growth stages were delayed because the principal effect of mulch was to reduce soil temperatures before full ground cover occurred, at least during the day.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicate that the major delay occurred at the recovery stage with delays in the subsequent stages being less and relatively constant. This is in agreement with Badaruddin et al (1999), who showed that growth stages were delayed because the principal effect of mulch was to reduce soil temperatures before full ground cover occurred, at least during the day.…”
Section: Resultssupporting
confidence: 92%
“…Crop residue mulches reduce evaporation of soil water primarily by shading the soil surface from the sun. Mulch will reduce evaporation most effectively early in the drying cycle when the surface soil is wet and early in the growing season when the leaf area is small (Bond & Willis, 1970; Adams et al , 1976; Badaruddin et al , 1999; Ji & Unger, 2001; Tao et al , 2006). Ramakrishna et al (2006) reported that, with mulch, soil moisture is higher and more uniform and that irrigation frequency can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Korem had cooler temperature than both Atsbi and MU sites (data not presented). Similar finding was reported by Badaruddin et al (1999) indicating that hotter environments elicit a greater response to applied treatments.…”
Section: Crop Phenologysupporting
confidence: 89%
“…The conventional management had greater HI than the ecological management, suggesting that early planting in the conventional management can increase grain yield more than total aboveground biomass yield. Late planting in the ecological management may have exposed maturing spring wheat to elevated temperatures and drought stress, resulting in reduced grain yield compared with the total biomass yield and therefore HI (Badaruddin et al, 1999; Reynolds et al, 2007). The HI varied among rotations in 2 out of 6 yr (Table 6).…”
Section: Resultsmentioning
confidence: 99%